Macrophage Polarization in the Development and Progression of Ovarian Cancers: An Overview - Cheng, Huiyan; Wang, Zhichao; Fu, Li; Xu, Tianmin (Frontiers in Oncology, 2019)
Ovarian cancer is a common type of gynecologic tumor and the most lethal gynecologic malignancy worldwide; the mortality rate of ovarian cancer has not decreased significantly in the past decades. Most patients are diagnosed at the late stages because of atypical symptoms and lacking the effective early diagnostic measures. The reasons for oncogenesis and development in ovarian cancer are not clear. Macrophages are immune cells derived from the innate immune system. Macrophages have two states of polarization (M1 and M2) that develop in response to different stimuli. The polarization and differentiation of macrophages into the cancer-inhibiting M1 and cancer-promoting M2 types are the basic events for the formation of the tumor microenvironment. The interaction of polarized macrophages with cancer cells plays a crucial role in a variety of cancers. However, the effects of macrophage M1/M2 polarization on ovarian cancer have not yet been systematically and fully discussed. In this review, we elucidated not only the occurrence, development and influences of macrophage polarization but also the association between macrophage polarization and ovarian cancer. The macrophage polarizing into the phenotypes M1 and M2 plays pivotal roles in ovarian cancer initiation, progression, and metastasis and provides targets for macrophage-centered treatment in the cancer microenvironment for ovarian cancer therapy. We also addressed the regulation of macrophage polarization in ovarian cancer via noncoding RNAs, exosomes and epigenetics.